Educational Philosophy of Islamic Hermeneutics and Its Application in Curriculum Studies - Robab Piri; Sadegh Maleki Avarsin (DAYAH: Journal of Islamic Education, 2022)
Hermeneutics is known as the science of interpreting and explaining texts. Hermeneutics, which was originally used as a way to interpret the scriptures and understand the text, has now risen to the level of a philosophical school and even entered the field of research theorizing and curriculum. It is especially important for disciplines about religious texts. For a hermeneutic educator, education is considered to be the heart of education, because education is nothing more than a process of effective application of hermeneutics (language) and for educators, it is a framework that may be used as a strategy and technique called critical thinking, which is a necessity of the present age. The first step of the article starts with extracting materials from the perspective of hermeneutic philosophy of Islamic approach by studying the internal and external texts of the curriculum dimensions and for this purpose the analytical-inferential method is used. In the second stage of the article, by examining the handful of patterns on hermeneutics that were deductive, theoretical, a new model for children's curriculum is presented to offer educators solutions to develop students' judgments and critical thinking from an early age. For this purpose, the practical analogy presented in a prescriptive form has been used as a useful and obligatory knowledge that has a great help in the field of education with an Islamic approach. This is provided that educators are familiar with the specific language of religious instruction, which requires skillful interpretations, so that students can learn how religious subjects influence people.